The Amendments in Typical Microbial Induced Soil Stabilization by Low-Grade Chemicals, Biopolymers and Other Additives: A Review. - Gowthaman, S.; Nawarathna, T.H.K.; Nayanthara, P.G.N.; Nakashima, S.; Kawasaki (Springer Nature, Singapore, 2021)
Soil with the required engineering properties is the first prerequisite in construction engineering, as the stability of the buildings and structures highly hinges on characteristics of soil by which they are supported. Microbial induced carbonate precipitation (MICP) is a newly developed soil improvement technique that has drawn the great deal of interest among geotechnical and geo-environmental engineers. The mechanism relies on set of biochemical reactions, utilizing bacterial enzyme to produce calcium carbonate bio-cement that could effectively bind the soil particles, leading to enhance the engineering properties of soil. Despite being a novel ground improvement technique, numerous studies have demonstrated that MICP can be a promising alternative for several geotechnical applications. Recently, researchers have started focusing on amending the typical MICP approach by incorporating preeminent materials, so that to enhance the MICP responses. This chapter presents a review on the amendments in MICP made by low-grade chemicals, biopolymers and other salient additives including magnesium ions, fly-ash and fibers. The effects and responses of the above materials in MICP are extensively described and discussed, and some research gaps are also pointed out. Although studies have suggested a wide range of advantages, there are many aspects and challenges on the above subjects are still to be addressed in future works prior to the real field applications.
Keywords: Soil; Bio cement; Low-grade chemicals; Biopolymers; Additives